Come home - Scottoline, Lisa (St. Martin's Press, 2012)
Jill Ruspolis is moving forward with her life after a devastating divorce. Her work as a doctor is hectic but fulfilling, she's newly engaged to a kind and loving medical researcher, and her daughter is finally happy again and doing well in school, in the aftermath of losing her stepfather in the divorce. But when Jill's distraught ex-stepdaughter Abby shows up on her doorstep with the news of her ex-husband's death from an apparent overdose, her life is thrust into turmoil once once again.